In situ solid-state synthesis of nitrogen-enriched porous carbon nanosheets from petroleum coke for lithium-ion hybrid capacitors - Benoy, Santhi Maria; Das, Anoushka K.; Sarmah, Debashis; Pawar, Meenakshi; Shelke, Manjusha V.; Saikia, Binoy K. (Energy & Fuels, 2025)
Lithium-ion capacitors (LICs) have emerged as a next-generation energy storage technology, offering a unique balance between the high energy density of lithium-ion batteries and the fast charge-discharge capability of supercapacitors. However, the development of high-performance anode materials remains a major challenge due to the trade-off between capacity, rate capability, and long-term cycling stability. Herein, we report a novel in situ solid-state synthesis approach for the scalable production of nitrogen-enriched porous carbon nanosheets (mBG1) from petroleum coke, an abundant industrial byproduct. The hierarchical porosity and optimized nitrogen functionalities of mBG1 facilitate rapid lithium-ion diffusion, enhanced electronic conductivity, and robust structural stability. Electrochemical characterization in lithium-ion half-cells demonstrates an exceptional specific capacity of 388 mAh g-1 at 0.1 A g-1, with an outstanding capacity retention of 92.7% over 1000 cycles (261.2 mAh g-1) at 1 A g-1. To validate its practical applicability, a full LIC coin cell was fabricated using mBG1 as the anode and commercial super activated carbon (super AC) as the cathode, achieving a specific capacitance of 44 F g-1 at 1 A g-1, a high energy density of 93.29 Wh kg-1 at 0.5 A g-1, and an impressive power density of 20.34 kW kg-1 at 10 A g-1, with 74% capacitance retention after 5000 cycles. The integration of ultrahigh nitrogen doping, hierarchical porosity, and scalable synthesis techniques offers a new pathway for designing next-generation lithium-ion capacitors with enhanced efficiency, stability, and economic viability. These findings establish mBG1 as a high-performance, scalable, and sustainable anode material for next-generation LICs, offering a transformative pathway for the valorization of petroleum coke in advanced energy storage applications.